Application of nanotechnology based-biosensors in analysis of wine compounds and control of wine quality and safety: A critical review - Hosnedlova, Bozena; Sochor, Jiri; Baron, Mojmir; Bjørklund, Geir; Kizek, Rene (Critical reviews in food science and nutriton, 2020)
Nanotechnology is one of the most promising future technologies for the food industry. Some of its applications have already been introduced in analytical techniques and food packaging technologies. This review summarizes existing knowledge about the implementation of nanotechnology in wine laboratory procedures. The focus is mainly on recent advancements in the design and development of nanomaterial-based sensors for wine compounds analysis and assessing wine safety. Nanotechnological approaches could be useful in the wine production process, to simplify wine analysis methods, and to improve the quality and safety of the final product.
Keywords: obaly potravin; Biosensing Techniques; Food Packaging; Wine; Nanostructures; Nanotechnology; biosenzitivní techniky; víno; nanostruktury; nanotechnologie